2013
DOI: 10.1016/j.heares.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the neurophysiological basis of auditory abilities for social communication: A perspective on the value of ethological paradigms

Abstract: Acoustic communication between animals requires them to detect, discriminate, and categorize conspecific or heterospecific vocalizations in their natural environment. Laboratory studies of the auditory-processing abilities that facilitate these tasks have typically employed a broad range of acoustic stimuli, ranging from natural sounds like vocalizations to “artificial” sounds like pure tones and noise bursts. However, even when using vocalizations, laboratory studies often test abilities like categorization i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 127 publications
(157 reference statements)
0
13
0
Order By: Relevance
“…This may include recognition of novel or low-probability sounds, which likely involves adaptive processes such as short-term depression for filtering out behaviorally-irrelevant sensory information (Ulanovsky et al, 2003; 2004; Wehr and Zador, 2005). Mechanisms of longer-term plasticity could be involved in processing the behavioral significance of certain sounds (Froemke and Martins, 2011; Froemke et al, 2013), as indicated by studies in trained animals (Buonomano and Merzenich, 1998) and by examination of pup call representations in virgin female mice compared to dams (Liu et al, 2006; Bennur et al, 2013; Rothschild et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…This may include recognition of novel or low-probability sounds, which likely involves adaptive processes such as short-term depression for filtering out behaviorally-irrelevant sensory information (Ulanovsky et al, 2003; 2004; Wehr and Zador, 2005). Mechanisms of longer-term plasticity could be involved in processing the behavioral significance of certain sounds (Froemke and Martins, 2011; Froemke et al, 2013), as indicated by studies in trained animals (Buonomano and Merzenich, 1998) and by examination of pup call representations in virgin female mice compared to dams (Liu et al, 2006; Bennur et al, 2013; Rothschild et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, even among nonsocial reinforcers, different receptive field effects are observed when appetitive instead of aversive operant conditioning is used (David et al, 2012). Much remains to be understood about how learning-related neuromodulatory systems are engaged to dynamically (Marlin et al, 2015; McGinley et al, 2015) or more persistently (Kilgard and Merzenich, 1998; Bao et al, 2001; Ji and Suga, 2003) alter AC responses to sounds, but the sensitivity to learning context motivates pursuing ethological paradigms to reveal intrinsic mechanisms of communication sound learning (Bennur et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, they did not receive consistent reinforcement when the test vocalization was a non-reference vocalization (C1Cx or G1Gx trials). That is, we wanted the monkeys to “spontaneously” (Bennur et al, 2013; Gifford et al, 2005) report whether the reference and non-reference vocalizations were the same or different. We hypothesized that this approach (Ghazanfar and Santos, 2004) would reveal information that would not be apparent had the monkeys been given consistent reinforcement whenever they reported that specific non-reference vocalizations were the same as or different from the reference vocalization.…”
Section: Discussionmentioning
confidence: 99%
“…We chose this strategy because we did not want to explicitly train the monkey to report that any particular non-reference vocalization (i.e., a coo Cx or a grunt Gx) was the same as or different from the reference vocalization (i.e., coo C1 or grunt G1). That is, the goal of this portion of the behavioral task was to allow monkeys to “spontaneously” (Bennur et al, 2013; Gifford et al, 2005) report whether the two vocalizations were the same or different.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation